THE NATURAL ECOSYSTEMS BETWEEN TOURIST EXPLOITATION AND DEGRADATION, CASE OF EL KALA NATIONAL PARK (ALGERIA) - Brahmi Sami; Grib Aissa (International Journal of Innovative Technologies in Social Science, 2024)
Algeria is the largest country in Africa by area and is among the countries in the world that possess a rich natural and cultural heritage due to its size, diversity of regions, environments, cultures, and the civilizations that passed through it, including Phoenicians, Romans, Vandals, Byzantines, Ottomans, and others. Our study area, the El Kala National Park, is one of the most important regions in Algeria with significant natural and cultural resources. It boasts an important coastal strip with numerous beautiful beaches and tourism expansion zones that could attract investors. Additionally, it contains various ecosystems, including lakes, dunes, forests, diverse flora and fauna and historical sites from different eras, most notably the El Kala Church.However, this heritage faces degradation due to irresponsible practices, such as the destruction of vegetation in summer 2022, despite existing protective laws. These challenges prompted our study, which partly examines Algeria's policies on tourism, environmental conservation, and heritage preservation. The research methodology employs a combined approach, starting with a historical analysis of the park's status since its UNESCO world heritage classification. We then address the natural ecosystems in the area, illustrated with images, and present a comprehensive study of tourism potentials. Finally, we conduct an in-depth analysis using the SWOT method to obtain a holistic view of the region's natural ecosystems and cultural heritage. Based on our findings, we offer conclusions and recommendations to promote tourism and drive regional development while preserving the ecosystems and natural and cultural heritage of El Kala National Park from degradation and damage.